Subject Doubling in the Slovenian Dialect of Resia. - Wandl, Florian (Journal of Slavic Linguistics)
This article focuses on the phenomenon of subject doubling in the Resian dialect of Slovenian, a Romance-Slavic contact variety spoken in northeastern Italy. Subject doubling involves the repetition of a subject phrase by a corresponding subject clitic, a feature rare within Slavic languages but attested in Resian and some neighboring Slovenian dialects due to prolonged contact with Romance languages, particularly Friulian. Based on a detailed analysis of a recent Resian translation of Antoine de Saint-Exupéry’s *The Little Prince*, the study finds that subject doubling in Resian occurs with a wide range of subject types—including nouns, personal pronouns (mainly second and third person), demonstratives, relatives, quantifiers, and numerals—without clear restrictions related to animacy, definiteness, or specificity. The placement of subject clitics is consistently preverbal and independent of the position of the doubled subject phrase, including in inverted clauses. The article argues that Resian subject doubling likely originated through language contact with Friulian but exhibits distinct patterns that do not fully align with implicational scales derived from Romance languages, highlighting the role of language-internal factors and contact-induced change in shaping this phenomenon.